2010
DOI: 10.1111/j.1365-2699.2010.02411.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the effects of the Pleistocene on the greater horseshoe bat, Rhinolophus ferrumequinum, in East Asia using ecological niche modelling and phylogenetic analyses

Abstract: Aim The extent to which the ranges of temperate biota in East Asia have been shaped by geological and climatic changes during the Pleistocene remains poorly understood. Previous molecular-based studies of the greater horseshoe bat (Rhinolophus ferrumequinum), which is widespread across China and Japan, suggest that this species was able to persist in multiple refugia in this region. However, limited availability of samples precluded a detailed analysis of past distributions. By integrating ecological niche mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 72 publications
(150 reference statements)
7
83
1
Order By: Relevance
“…Thus the Yangtze plains region was likely to be a glacial refuge, supporting our hypothesis that such refugia existed in eastern China during the Pleistocene. Other studies have also confirmed that mountainous areas of this region had relatively stable climatic conditions during the Pleistocene glaciation, providing probable glacial refugia for many species [14,28]. Our study identifies that intra-specific divergence within M. pilosus first occurred in 0.25-0.19 Myr BP (Clade A), which corresponds to a relatively warm interglacial period in mainland China [29].…”
Section: Discussionsupporting
confidence: 80%
“…Thus the Yangtze plains region was likely to be a glacial refuge, supporting our hypothesis that such refugia existed in eastern China during the Pleistocene. Other studies have also confirmed that mountainous areas of this region had relatively stable climatic conditions during the Pleistocene glaciation, providing probable glacial refugia for many species [14,28]. Our study identifies that intra-specific divergence within M. pilosus first occurred in 0.25-0.19 Myr BP (Clade A), which corresponds to a relatively warm interglacial period in mainland China [29].…”
Section: Discussionsupporting
confidence: 80%
“…6). Evidence for a number of these postulated glacial refugia has been reported in previous studies for many organisms, including bats (Flanders et al 2011;Khan et al 2010;Lin et al 2014;Mao et al 2013). Accordingly, we propose that the contraction of woody bamboo forests into different glacial refugia had fragmented the distribution of the Pliocene ancestors of both T. pachypus s. lat.…”
Section: The Evolution Of Tylonyteris Spp In Southeast Asia During Tmentioning
confidence: 81%
“…Экземпляры из четырех популяций восточной Азии (Чеджу, континентальная Корея, севе-ро-восточный Китай и Япония) образуют одну слабо подразделенную дальневосточную кладу, were recognized from mtDNA ND2 gene and microsatellite analyses (Flanders et al, 2009). The further study of the same markers (Flanders et al, 2011) reported three lineages in East Asia: central China lineage from Shaanxi, Sichuan, Yunnan, and Hubei; eastern China lineage from Anhui, Jiangxi, Shandong, Henan, Hubei, and Beijing; and Japan lineage from Japan, Jilin, and Shandong. We found that both results are not consistent in the designation of the eastern China and Japan lineages (i.e., from their successive studies the Beijing sample, recognized initially as the Japan lineage, moved to the eastern China lineage, and the Shandong samples, found initially as the eastern China lineage, moved to both eastern China and Japan lineages).…”
mentioning
confidence: 95%
“…On the other hand, Lopez et al (1997) reported that regarding evolutionary rates, the cytochrome b gene vary at a slower rate than the control region and ND2, and Flanders et al (2009Flanders et al ( , 2011 noted that further sampling of R. ferrumequinum from northern China and Korea is needed before colonization pattern in fareastern Asia can be fully resolved. Thus, it is necessary to obtain sequences of conservative cytochrome b gene from Korean R. ferrumequinum specimens in order to reexamine population differentiation of R. ferrumequinum from far-eastern Asia and other regions as well.…”
mentioning
confidence: 99%